The Analyses of Chemical Components From Oldenlandia hedyotidea (DC.) Hand.-Mazz and Anticancer Effects in vitro - Chuanyi Zhao; Mengyuan Wei; Yilin Zheng; Weili Tao; Qian Lv; Qiongjin Wang; Shuyun Wang; Yicun Chen (Frontiers Media S.A., 2021)
Oldenlandia hedyotidea (DC.) Hand.-Mazz (OH), also known as sweet tea, is a valuable functional food with medicinal properties and is used for the treatment of cold, cough, gastroenteritis, heatstroke, herpes zoster, and rheumatoid arthritis. The phytochemicals in plant-based foods are responsible for the occurrence of these diseases to some extent. However, there is a scarcity of information on the chemical components of OH. We, therefore, aimed to investigate the phytochemical components of OH using ultra high-performance liquid chromatography-mass spectrometry (UHPLC-MS) and UHPLC triple time-of-flight mass spectrometry (UHPLC-Triple-TOF-MS). The main component of the OH extract, asperulosidic acid, was additionally quantified using UHPLC with ultraviolet detection (UHPLC-UV). The anticancer activity of the OH extract was assessed by a cell proliferation assay and a scratch assay using an esophageal cancer cell line. Ten compounds were tentatively identified in the aqueous extract of OH, including five iridoids, two anthraquinones, and one phenolic acid. The content of asperulosidic acid in the aqueous extract of OH was approximately 42 μg ml−1, and the extract exerted definite in vitro anticancer effects. The results can be used for quality control and assessment of the OH extract, which can serve as a promising source of functional ingredients for potential use in the food and drug industries.